FROM SELF-CARE TO OVERINDULGENCE: INVESTIGATING THE BIOPSYCHOSOCIAL DIMENSIONS OF SKINCARE ADDICTION - Usman Jaffer; Sara Malyana Hanisofian; Nur Syahmina Athirah Muhamad Zaib; Nur Atifah Syazwani Sapian; Siti Zulaikha Ismadi; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Skincare, traditionally perceived as a self-care practice for promoting healthy skin, has recently emerged as a potential behavioural addiction. This paper explores the multifaceted nature of skincare addiction by examining its psychological, physiological, and social underpinnings. First, the discussion highlights how stress and coping strategies can inadvertently foster compulsive product usage, especially when individuals seek immediate relief or improved self-image. Second, it underscores how fear of missing out (FOMO), marketing tactics, and entrenched beauty standards contribute to impulsive buying and overuse of products. Third, the review demonstrates how positive emotions, enhanced self-esteem, and emotional attachment to skincare products activate neural reward circuits, further reinforcing potentially addictive behaviours. Drawing on relevant case studies, the paper contextualizes these factors within contemporary social media-driven marketing ecosystems. Lastly, it proposes preventative measures and interventions—ranging from cognitive-behavioural therapy to stricter policy regulations—aimed at mitigating the risk of compulsive skincare behaviours. By synthesizing existing theoretical and empirical insights, this work seeks to advance the understanding of skincare addiction and encourage further research on emerging behavioural dependencies.